Pengaruh Struktur Kepemilikan Terhadap Agresivitas Pajak Pada Perusahaan Manufaktur di Indonesia - Vandalucia Faradhilah Verose; Isna Putri Rahmawati (JRAK: Journal of Accounting Research and Computerized Accounting, 2022)
This study aims to determine the effect of corporate ownership structure consisting of concentrated ownership, government ownership, institutional ownership, and foreign ownership on tax aggressiveness. The total sample used in this study is 200 taken from manufacturing companies listed on the Indonesia Stock Exchange from 2018 to 2019. The results found that concentrated and foreign ownership had a negative effect on tax aggressiveness, while institutional ownership had a positive effect on tax aggressiveness. Meanwhile, government ownership has no significant effect on tax aggressiveness.